Pemberdayaan Yakult Lady Dalam Meningkatkan Penjualan Melalui Strategi Pemasaran Direct Selling - Adzraa Tsabita Nailla Rachmi; Adi Saputra; Nur Aeni Fatimah; Belinda Vania Putri; Ahmad Rohidin; Riyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This community service activity aims to examine the implementation of Customer Experience Management (CEM) at PT Yakult Indonesia Persada through the role of Yakult Ladies and the direct selling system in fostering customer loyalty. Field observations were conducted at the Yakult distribution center in Mojokerto. The results indicate that the Yakult Lady program not only serves as a product distribution system but also strengthens emotional connections with consumers through personal interaction. The direct selling system also proves effective in maintaining distribution efficiency and product quality. Both strategies significantly contribute to enhancing customer trust, repeat purchases, and brand loyalty. Recommendations include strengthening the capacity of Yakult Ladies through training, utilizing digital technology for customer data management, and expanding distribution coverage to rural areas. This activity provides practical benefits for the development of customer experience–based marketing strategies and the improvement of service quality in the community.